Two minor revisions:

## inhibit rearrangement

Context() -> reduction -> set( '(-x)+y' => 0, '(-x)-y' => 0 ) ;

## repeat reduction of $poly to remove parentheses

## around constant if it is the last term

$poly = Compute( "$poly" ) -> reduce ;

I suspect the first use of reduce would replace "+ (-5 x^0)" with "+ (-5)" and the second reduce yields "- 5". It is unclear why the second step is not needed if the constant is not the last term.

## WeBWorK Problems

### Q: random polynomial

This forum has a limit to the number of forum postings you can make in a given time period - this is currently set at 10 posting(s) in 1 day